The Effect of Back Massage with Virgin Coconut Oil (VCO) on the Intensity of Labor Pain in the First Active Phase at PMB Restu Bunda Gunung Terang District, West Tulang Bawang Regency - Pipit Yulia Puspita; Iis Tri Utami; Inggit Primadevi; Prisiari Kusuma Wardani; Eva Fatmaati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Childbirth is often perceived as frightening and causing extreme pain. Some mothers also feel traumatized by their first childbirth process because of various difficulties and pain during childbirth so that they are reluctant to plan to have children again. Labor pain is caused by uterine contractions and dilation of the cervix and lower uterine segment. Survey data from PMB Restu Bunda in 2024 on 5 mothers who gave birth, it was found that overall respondents experienced pain, as many as 3 people with a pain scale of 7 (severe pain) and as many as 2 people with a pain scale of 6 (moderate pain). One non-pharmacological therapy that can reduce the intensity of pain is back massage using Virgin Coconut Oil (VCO). The research objective was to determine the effect of back massage with Virgin Coconut Oil (VCO) on the intensity of active labor pain in the first stage of labor at the IMP Restu Bunda Gunung Terang Sub-District of West Tulang Bawang Regency. The quantitative research type is a pre-experimental design, one group pre-test - post-test design. The population in this study were all mothers who were going to give birth, as many as 22 mothers, with a sample of 18 people taken by accidental sampling. The study was conducted at the IMP Restu Bunda of Gunung Terang Sub-District West Tulang Bawang Regency. Data collection used observation sheets. Data analysis was carried out using univariate and bivariate tests (Wilcoxon test). The study results showed that the average labor pain before being given a back massage with virgin coconut oil (VCO) was 7.0 and after being given a back massage with virgin coconut oil (VCO) was 5.2. There was an influence of back massage with virgin coconut oil (VCO) on the intensity of active labor pain in the first stage at the IMP Restu Bunda of Gunung Terang Sub-District of West Tulang Bawang Regency with a p-value = 0.001 (p-value <α = 0.05). Suggestions for health workers can recommend back massage with virgin coconut oil (VCO) can be used as complementary therapy for mothers in the first stage of labor.